Recent Trends in Fractal Antenna Research for In-body Communications - Muhammad Miftahul Amri; Ghafar Ramadhan Faqih (The Indonesian Institute of Science and Technology Research, 2022)
Fractal structure is a unique geometry that can be seen in many objects in nature, such as clouds, coastlines, DNA, trees, and even pineapple. This structure has manifold geometries, self-similarities, and space-filling properties. Due to these properties, fractal geometries are preferred to miniaturize an antenna in wireless communications. There are many cases that require a small compact antenna, including in-body communications. In this article, we present a review of the recent trends and advancements in fractal antenna research, especially in the miniaturization of implantable antennas for in-body communications. The review is derived from articles that are gathered from online libraries such as IEEE, PubMed, Nature, MDPI, Elsevier, and Google Scholar. As a result, we have collected more than 60 articles related to fractal-implantable antenna and in-body communications. Indeed, many researchers have proposed an implantable compact antenna with fractal geometries in the last decades. Fractal geometry allows a longer electrical length to be routed in a smaller area of the antenna. However, several things remain challenging in designing a fractal antenna, including bandwidth, fabrication complexity, and intercell interference.